Ultrasound assessments of organs and blood vessels before and after 40 days isolation in a cavern (deep time experiment 2021) - Arbeille, Philippe; Zuj, Kathryn A.; Besnard, Stephane; Mauvieux, Benoit; Hingrand, Corentin; Delaunay, Pierre-Louis; Hughson, Richard L.; Clot, Christian (Frontiers in Physiology, 2023)
Spaceflight simulation studies like confinement in small volume habitat with limited physical activity have reported even after 60 days an abnormal arterial wall adaptation with increase thickness or stiffness. The purpose of the current study was to determine the effects on blood vessel and organ structure of 40 days of isolation in a huge habitat with intensive physical activity. Data were collected from 14 individuals (7 male) who isolated in a cavern for 40-days while performing normal daily activities without time references. Ultrasound assessments were performed pre- and post-isolation using a teleoperated system with eight different acoustic windows to obtain 19 measurements on 12 different organ/vascular structures which included the common carotid artery, femoral artery, tibial artery, jugular vein, portal vein, bile duct, kidney, pancreas, abdominal aorta, cervical and lumbar vertebral distance, and Achilles tendon. Common carotid artery measures, including the intima media thickness, stiffness index, and the index of reflectivity measured from the radiofrequency signal, were not changed with isolation. Similarly, no differences were found for femoral artery measurements or measurements of any of the other organs/vessels assessed. There were no sex differences for any of the assessments. Results from this study indicate a lack of physiological effects of 40-days of isolation in a cavern, contrary to what observed in previous 60d confinement. This suggests a potential protective effect of sustained physical activity, or reduced environmental stress inside the huge volume of the confined facility.